(untitled) (Polish Yearbook of International Law, 2017)
This article aims to investigate the phenomenon of the rule of law promotion exercised by the EU through the Deep and Comprehensive Free Trade Agreements (DCFTAs). First, the article emphasizes the unique combination of normative and market power the EU uses to diﬀuse its norms through trade liberalization. Next, it provides an insight into the particularities of the European Neighbourhood Policy as a policy context for the conclusion and implementation of the Association Agreements, including the DCFTAs with Ukraine, Moldova and Georgia, as well as the conceptual problematic and scope of the rule of law as a value the EU seeks to externalize. Using the DCFTAs with Ukraine, Moldova, and Georgia) as a single group case study of the transparency dimension of the rule of law, the central part of the article analyzes the DCFTAs substantive requirements, directed toward promoting transparency in the partner states (while categorizing the requirements into the most general ones; cooperationrelated; and disciplinespecifc) and the legal mechanisms that make these clauses operational (e.g., the institutional framework of the AAs, gradual approximation and monitoring clauses, and the Dispute Settlement Mechanism). In concluding, the article summarizes the stateoftheart of the rule of law promotion through the DCFTAs, distinguishes the major challenges the respective phenomenonfaces, and emphasizes the prospects for and difculties of using the DCFTAs as an instrument of rule of law promotion.